Gender Based Study: Science Processing Skills of Eight Grade Students in Government and Private Schools of Muzaffarabad - Khursheed, Kashif; Zia, Asma; khurshid, Rabia (JSE, 2025)
The current research aims to examine 8th-grade students’ science processing skills in Muzaffarabad’s Government and Private schools. The nature of the study was quantitative. A random sampling strategy was used to select 20 schools (10 private and 10 Government). There were 140 students in the sample, 70 of whom were male and the remaining 70 were female. From 70 male students, 35 students were drawn from five Government schools, with seven students from each school, and the same process was used for selecting the female students from five private schools. An achievement test containing questions of basic Science Process Skills was used as a research instrument. As a research instrument, an achievement test was used. So, for developing an achievement test science book of class 8th was studied by researcher, and many websites too. After these activities, an achievement test initial draft was developed by the researcher with the help of a respected supervisor. An achievement test comprised of six fundamental Science Process Skills. Observing, Classifying, Measuring, Communicating, Inferring, Predicting. For comparing the achievement test results, the Independent Sample t-test was used. When comparing more than two groups in this study, one ANOVA was used. Results of this research showed that the female students were better on science process skills compared to male science students. And the levels of private schools’ performances were higher than the performances of the Government schools with respect to science processing skills.